Grab That Mike: communicative issues in French talk show - Van Son, Ludwina (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
In this analysis we have chosen a recent French talk show to illustrate how communication is turned into some new kind of "ideology"nowadays: in other words, you have to communicate if you consider yourself a citizen of today's world. The main characteristic of issue-centered talk shows being the destabilization of the implicit rules and participation framework, we observe how the so-called democratic right to express ourselves is (mis)used by the talk show host to secure the dynamics of the show. In order to reveal the host's manipulations, we have examined the verbal interactions between host and guests on the following issues: topic choice, turn-taking mechanisms and identity construction of the talk show's guests. In the perspective that this kind of talk show presents itself as a public space where direct democracy can be exercised, the analysis of the discursive strategies of the talk show host reveals the impact of a mediatic participation framework.